2017
DOI: 10.3233/bmr-169588
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pain severity on postural stability and dynamic limits of stability in chronic low back pain

Abstract: The intensity of pain has shown to be one of the determinants affecting dynamic balance in chronic LBP patients who showed differences in the impairment of PSIs and LOS with different degrees of pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 36 publications
1
13
1
5
Order By: Relevance
“…It is also well-known that improper postural stability leads to higher injury risk during sports activity [10,19]. Soliman ES et al and Ruhe A et al stated that the severity of pain was one of the determinants affecting dynamic balance and postural sway in patients with LBP [20,21]. Our study did not reveal correlation between intensity of LBP pain and postural stability.…”
Section: Discussioncontrasting
confidence: 57%
“…It is also well-known that improper postural stability leads to higher injury risk during sports activity [10,19]. Soliman ES et al and Ruhe A et al stated that the severity of pain was one of the determinants affecting dynamic balance and postural sway in patients with LBP [20,21]. Our study did not reveal correlation between intensity of LBP pain and postural stability.…”
Section: Discussioncontrasting
confidence: 57%
“…Some studies show a reduced body balance in back pain subjects compared to healthy individuals [ 67 ]. In the current study, it was not possible to distinguish between back pain participants and subjects with a “healthy back” using the MFT-S1-Checklist system.…”
Section: Discussionmentioning
confidence: 99%
“…Age is an essential factor in evaluating postural balance. There are studies in the literature indicating that age is not effective on balance in young adults (3,5,10), while other studies are indicating that balance disorders increase with age; therefore, in the literature, age-related changes in postural sway are still controversial (16). Lizama et al (17), investigated the effect of age on balance responsiveness, eyes open and eyes closed, in younger and older healthy subjects who had no balance impairments.…”
Section: Discussionmentioning
confidence: 99%
“…Postural control is essential for stability and balance during standing (1). Balance disorders are found to be associated with various orthopedic problems such as back pain, neck pain or ankle injuries (2,3). It has been also reported that the incidence of many orthopedic injuries is higher in middle-aged people, women, and obese individuals (4).…”
Section: Introductionmentioning
confidence: 99%